Pengaruh Kepemilikan Aplikasi Mobile Banking Dan Gaya Hidup Terhadap Perilaku Konsumtif Di Kalangan Mahasiswa - Novianti Hasibuan, Janiah; Aulia Risky, Winda; Lestari, Sry; Angraini, Ririn (Fakultas Ekonomi dan Bisnis Islam, 2025)
The formulation of the problem in this study is whether there is an effect of ownership of mobile banking applications and lifestyle on consumptive behavior among students. This study aims to determine whether there is an effect of ownership of mobile banking applications and lifestyle partially and simultaneously on consumptive behavior among students. The research methodology used is a quantitative approach with a survey method. The population of this study were all active students in Padangsidimpuan City with a sample of 100 students. The sampling technique used incidental sampling. The data collection technique used a questionnaire and then data processing using SPSS version 26.0 software. Data analysis using multiple linear regression. The results showed that there was no significant effect of ownership of mobile banking applications on consumptive behavior among students.